2017
DOI: 10.1590/s1678-9946201759070
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance, AmpC-β-lactamase and extended-spectrum β-lactamase-producing Enterobacteriaceae isolated from fish and shrimp

Abstract: The present study aims to detect the production of extended-spectrum beta-lactamases (ESBL) by enterobacteria isolated from samples of fresh shrimp and fish obtained from the retail trade of the city of Sobral, Ceará State, Brazil. All bacterial isolates were submitted to identification and antimicrobial susceptibility testing using aminopenicillin, beta-lactamase inhibitors, carbapenem, 1st, 2nd, 3rd and 4th generation cephalosporins, and monobactam. Three types of beta-lactamases - ESBL, AmpC and KPC - were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…In this study, 30% of the isolates were resistant to this antibiotic. However, de Almeida et al [34] reported a single isolate resistant to Ceftriaxone and Verner-Jeffreys et al [35] reported all the isolates susceptible to it, which are contrasting to current findings. In this study, 9.6% isolates were resistant to trimethoprim-sulfamethoxazole, a bactericidal drug which works by inhibiting folic acid synthesis.…”
Section: Biochemical Identificationcontrasting
confidence: 89%
“…In this study, 30% of the isolates were resistant to this antibiotic. However, de Almeida et al [34] reported a single isolate resistant to Ceftriaxone and Verner-Jeffreys et al [35] reported all the isolates susceptible to it, which are contrasting to current findings. In this study, 9.6% isolates were resistant to trimethoprim-sulfamethoxazole, a bactericidal drug which works by inhibiting folic acid synthesis.…”
Section: Biochemical Identificationcontrasting
confidence: 89%
“…Several studies revealed a high prevalence of non-susceptibility to this class of antibiotic in fish, shrimps and water samples from aquaculture farms. These studies reported the discovery of bla SHV and bla TEM genes, associated with β-lactam non-susceptibility [ 91 , 92 , 93 , 94 ]. In our study, β-lactam resistance genes were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemistry has increased the number of β-lactamase enzymes with enlarged substrate specificities [ 129 ]. The substrate range includes cephalosporins (cefotaxime, ceftriaxone [ 130 , 131 , 132 ]), monobactam aztreonam [ 133 , 134 , 135 ], amino-penicillin combinations [ 136 ], lactamase inhibitor ampicillin-sulbactam [ 137 , 138 , 139 , 140 ], ureido-penicillins [ 141 , 142 ] including piperacillin/tazobactam [ 143 , 144 , 145 , 146 ], temocillin [ 147 ], piperacillin/tazobactam [ 148 ], and ceftolozane-tazobactam [ 149 ]. Furthermore, the appearance of new enzymes is not associated with the loss of ability to hydrolyze the earlier lactams, such as ampicillin [ 36 ].…”
Section: Resistance Problems Related To Gram-negative Pathogensmentioning
confidence: 99%